(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The success of a space mission where the satellite must perform rapid attitude maneuvers with great angles is extremely dependent of a careful investigation of theÂ nonlinear dynamics of the satellite. Since these big maneuvers imply in the dynamic couplingÂ between the satellites angular motion and the actuators such as reaction wheels and/or gasÂ jets. As a result, this coupling must be taking into account in the Attitude Control SystemÂ (ACS) design. This paper presents the nonlinear model derivation of a rigid satellite and theÂ performance comparison of two controllers designed by Lyapunov and LQR methods. The dynamics of the satellite is initially derived in the non-linear Euler equations form and theÂ kinematics is based on the quaternion parametrization which represent the rotation andÂ attitude motion, respectively. In the sequel, the linear model is obtained where linearization isÂ about an operating point of the arbitrary angular velocity and the reaction wheel angularÂ momentum. From this model, several simulations are performed in order to investigate theÂ influence of the nonlinear dynamics in the in the SCA performance which is designed by trialÂ and error and by the Linear Quadratic Regulator approaches. The ACS performance isÂ evaluated considering the capacity of the reaction wheels to maintain the stability and toÂ control the angular velocity and the attitude of the satellite. The stability is investigatedÂ comparing the location of the poles and zeros of the open and closed loops. The ACSÂ performance is evaluated comparing the amount of energy spend by each control law. Keywords: Satellite Control, nonlinear dynamics, LQR and Lyapunov theory